DUI histories in intoxicated injured bicyclists. Issue 4 (October 2016) - Maximus, Steven; Figueroa, Cesar; Pham, Jacqueline; Kuncir, Eric; Barrios, Cristobal
Abstract : INTRODUCTION: It has been well documented that the use of alcohol correlates with injury risk, especially in DUI (driving under the influence) and DWI (driving while intoxicated). Consumption of alcohol in patients presenting with bicycle-related injuries is associated with greater injury severity, longer hospitalization, and higher health care costs. We hypothesized that intoxicated patients operating a bicycle with traumatic injuries have previous DUI or DWI convictions and had lost their privilege to drive a motor vehicle, resorted to bicycling, and had continued alcohol consumption despite negative previous consequences. METHODS: We retrospectively collected data on injured bicyclists older than 18 years with positive blood alcohol content levels treated from the period January 2009 to June 2014 at a large Level 1 urban trauma center. We then matched each patient by name and date of birth and were able to obtain public criminal records through the Superior Court of California for the local of county. RESULTS: A total of 149 injured bicyclists with positive blood alcohol levels were identified. Their average blood alcohol content was 236.0 mg/dL, and their average age was 41 years. Sixty-six (44.2%) of these patients had prior DUI/DWI convictions with suspension of driving privileges. Ninety-five patients in this group (63.8%) had no health insurance, and 51 patients (34.2%) tested positive for other drugs. Intoxicated bicyclists trended toward longer hospital length compared with nonintoxicated bicyclists (4.60 vs. 3.44 days; p = 0.07). Three (0.02%) of 149 patients were charged with bicycling while intoxicated. CONCLUSION: Intoxicated bicyclists involved in trauma are more likely to have a previous DUI/DWI, have other drug use, tend to have longer hospital stays, and are less likely to have insurance. Bicycle safety education and behavior modification targeting DUI/DWI offenders are warranted. In order to promote injury prevention, resources to increase awareness of this underestimated public health issue should be promoted. LEVEL OF EVIDENCE: Epidemiologic study, level III.